Determinants of depression and anxiety among type 2 diabetes patients in governments’ hospitals at Harari regional state, Eastern Ethiopia: A multi-center cross-sectional study - Kabtamu Nigussie; Addisu Sertsu; Galana Mamo Ayana; Yadeta Dessie; Tilahun Bete; Lemesa Abdisa; Gebiso Roba Debele; Dawud Wadaje; Abraham Negash (BMC Psychiatry, 2023)
Abstract Background Type 2 diabetes mellitus is the most common health problem globally. Depression and anxiety can exacerbate disease complications, make patients suffer more, and increase healthcare costs. Even though, depression and anxiety are common among type 2 diabetes mellitus patients, there have been limited studies conducted about the determinants of depression and anxiety in Ethiopia. Therefore, the purpose of this study was to assess the magnitude and determinants of depression and anxiety symptoms among Type 2 diabetes mellitus patients, attending out-patient treatment at Harari regional state government hospitals, Eastern Ethiopia. Method An institutional based cross-sectional study was conducted from March to April at Harari regional state government hospitals in eastern Ethiopia. A total of 421 participants were recruited using the systematic sampling technique. Data was collected by using Afan Oromo version of interviewer-administered structured and semi-structured questionnaires. Depression and Anxiety symptoms were assessed by the Hospital Anxiety and Depression Scale. Bivariate and multivariate logistic regression analysis was done to identify variables related to both depression and anxiety symptoms. The association was described using an adjusted odds ratio and a 95% confidence interval (CI), with P-values of 0.05 used as a cutoff for a significant association in the adjusted analysis. Result Out of the 416 participants included in this study, 42.3%, 40.4% had depression and anxiety symptoms, respectively. Being female (Adjusted Odds Ratio = 1.85(1.09–3.15)), no formal education (Adjusted Odds Ratio = 2.65, (1.04–6.73)), age ≥ 70 (Adjusted Odds Ratio = 2.88 (1.28–6.48)), family history of mental illness (Adjusted Odds Ratio = 1.71 (1.35–3.82)) and poor social support (Adjusted Odds Ratio = 2.35(1.12–6.03)) were statistically associated with depression. While having a family history of mental illness (AOR 1.74(1.03–2.95)), being widowed (AOR = 3.45(1.49–8.01)), and having poor social support (AOR = 2.15(1.12, 4.89)) were statistically significant associated with anxiety at a p-value < 0.05. Conclusion Current study results showed that the magnitude of depression and anxiety were relatively high among type 2 diabetes mellitus patients.Having a family history of mental illness and poor social support were statistically associated with both depression and anxiety symptoms. Screening, early detection, and appropriate treatment of depression and anxiety symptoms in type 2 diabetes mellitus patients should be prioritized by health care providers.